Cluster observations of kinetic structures and electron acceleration within a dynamic plasma bubble. Issue 2 (11th February 2013) - Zhou, Meng; Deng, Xiaohua; Ashour‐Abdalla, Maha; Walker, Raymond; Pang, Ye; Tang, Chaoling; Huang, Shiyong; El‐Alaoui, Mostafa; Yuan, Zhigang; Li, Huimin
Abstract : [1] Fast plasma flows are believed to play important roles in transporting mass, momentum, and energy in the magnetotail during active periods, such as the magnetospheric substorms. In this paper, we present Cluster observations of a plasma‐depleted flux tube, i.e., a plasma bubble associated with fast plasma flow before the onset of a substorm in the near‐Earth tail around X  = −18  RE . The bubble is bounded by both sharp leading (∂ bz /∂ x  < 0) and trailing (∂ bz /∂ x  > 0) edges. The two edges are thin current layers (approximately ion inertial length) that carry not only intense perpendicular current but also field‐aligned current. The leading edge is a dipolarization front (DF) within a slow plasma flow, while the trailing edge is embedded in a super‐Alfvénic convective ion jet. The electron jet speed exceeds the ion flow speed thus producing a large tangential current at the trailing edge. The electron drift is primarily given by the E × B drift. Interestingly, the trailing edge moves faster than the leading edge, which causes shrinking of the bubble and local flux pileup inside the bubble. This resulted in a further intensification of B z, or a secondary dipolarization. Both the leading and trailing edges are tangential discontinuities that confine the electrons inside the bubble. Strong electron acceleration occurred corresponding to the secondary dipolarization, with perpendicular fluxes dominating the field‐aligned fluxes. We suggest that betatron acceleration is responsible for the electron energization. Whistler waves and lower hybrid drift waves were identified inside the bubble. Their generation mechanisms and potential roles in electron dynamics are discussed. Key Points: The bubble is bounded by both leading and trailing edges The interaction between leading and trailing edge leads to a secondary DF Electron acceleration occurred at the secondary DF